Variabilidad genetica de aislamientos colombianos del Potato Mop-Top Virus (PMTV) - Osorio Giraldo, I.=700 1 Gutierrez Sanchez, I.; Marin Montoya, M.
(Es, En)
Ilus., 43 ref.
Keywords: SOLANUM TUBEROSUM; VARIACION GENETICA; PCR; COSTA RICA; RT-PCR; SECUENCIACION